Coaxial nanofiber for improving gastrointestinal resistance of probiotics and preparation method of coaxial nanofiber

By wrapping the ethyl cellulose shell layer and the core layer of probiotics in the lactic acid bacteria, coaxial nanofibers with core-shell structures are formed, the problems of lactic acid bacteria preparation stability and anti-gastrointestinal fluid stress are solved, and the functional effect of the product is improved.

CN119194657APending Publication Date: 2024-12-27NORTHEAST AGRICULTURAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411334490.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In traditional production methods, lactic acid bacteria preparations have poor stability and low effective viable bacteria content. They are difficult to resist the stress of gastric and intestinal fluid after entering the animal's digestive tract, resulting in poor functional effect.

Method used

The preparation method of coaxial nanofibers is adopted to form nanofibers with core-shell structures by encapsulating probiotics in the shell of ethyl cellulose and using dihydrobamates to improve thermal stability and stress resistance.

Benefits of technology

It significantly improves the thermal stability and anti-gastrointestinal fluid stress ability of probiotics, ensures reasonable release under alkaline conditions, and improves the functional effect of probiotic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194657A_ABST
    Figure CN119194657A_ABST
Patent Text Reader

Abstract

The invention relates to the field of probiotic delivery systems, in particular to coaxial nanofibers capable of improving gastrointestinal resistance of probiotics and a preparation method of the coaxial nanofibers. According to the preparation method, dihydromyricetin is added into the electrostatic spinning solution containing probiotics, and then the dihydromyricetin is wrapped with the ethyl cellulose solution, so that the thermal stability of the probiotics is remarkably improved, meanwhile, the probiotics can be protected from resisting stress of gastric juice and intestinal juice, and the functional effect of a probiotic product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of probiotic delivery systems, and in particular to a coaxial nanofiber for improving the gastrointestinal resistance of probiotics and a preparation method thereof. Background Art

[0002] In recent years, as people gradually realize the many disadvantages of antibiotics and countries around the world have successively banned the use of antibiotics in feed, probiotic preparations have received more and more attention and have good development prospects. Among them, lactic acid bacteria are the most widely used. As we all know, lactic acid bacteria are normal flora in the intestines of humans and animals, and are closely related to the health of animals. At present, a large number of studies have shown that lactic acid bacteria preparations have good biological functions, and have been proven to be able to treat and prevent certain intestinal diseases of animals or play a health-care role in clinical practice, and have also been widely used in the feed industry.

[0003] However, the traditional production method of lactic acid bacteria preparations is to activate the preserved strains and then carry out liquid fermentation to expand the culture, and then apply it to production. The lactic acid bacteria products prepared by this method are slightly less stable and have a slightly lower content of effective live bacteria. This is because: on the one hand, lactic acid bacteria cannot form spores during growth, and have poor resistance. In addition, during its life activities, it will also produce some metabolites such as lactic acid and acetic acid that endanger its normal growth and reproduction, so it is difficult to preserve for a long time under liquid conditions; on the other hand, after lactic acid bacteria enter the animal digestive tract, the low pH gastric juice and bile salts in the intestinal juice will also cause damage to it, making it difficult to have enough live bacteria to reach and settle in the intestine to better play a probiotic role. Therefore, how to improve the functional effects of probiotic products is a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention

[0004] The purpose of the present invention is to provide a coaxial nanofiber for improving the gastrointestinal resistance of probiotics and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art. The coaxial nanofiber for improving the gastrointestinal resistance of probiotics prepared by the preparation method provided by the present invention can better protect the probiotics from the stress of gastric juice and intestinal juice, and improve the functional effect of the probiotic product.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] The present invention provides a method for preparing coaxial nanofibers for improving the gastrointestinal resistance of probiotics, comprising the following steps:

[0007] (1) mixing a polyvinyl alcohol solution and fucoidan to obtain a PVA / FUC solution;

[0008] (2) mixing the PVA / FUC solution with dihydromyricetin to obtain a blended solution of the three;

[0009] (3) mixing the three blended solutions and probiotics to obtain a nuclear layer solution;

[0010] (4) mixing ethyl cellulose and acetic acid to obtain a shell solution;

[0011] (5) After placing the core layer solution inside the coaxial needle and placing the shell layer solution outside the coaxial needle, the core layer solution and the shell layer solution are mixed at a flow rate ratio of 1:(1-2) to obtain a solution containing the coaxial nanofibers.

[0012] Preferably, in step (1), the mass percentage of polyvinyl alcohol in the polyvinyl alcohol solution is 10%; the mass percentage of fucoidan in the PVA / FUC solution is 3%.

[0013] Preferably, in step (2), the mass percentage of dihydromyricetin in the three-mixed solution is 0.16%.

[0014] Preferably, in step (3), the effective viable count in the nuclear layer solution is 10 9 -10 10 1 g CFU / mL; the probiotic is Lactobacillus plantarum.

[0015] Preferably, in step (3), the probiotic is Lactobacillus plantarum.

[0016] Preferably, in step (4), the mass percentage of ethyl cellulose in the shell solution is 40%.

[0017] Preferably, the abiotic stress includes the ability to resist gastric fluid stress and the ability to resist intestinal fluid stress.

[0018] The present invention provides a coaxial nanofiber prepared by the above preparation method.

[0019] The present invention provides application of the above coaxial nanofibers in preparing medicines.

[0020] The present invention discloses the following technical effects:

[0021] The present invention adds dihydromyricetin to an electrospinning solution containing probiotics and then wraps the solution with an ethyl cellulose solution, thereby significantly improving the thermal stability of the probiotics and protecting the probiotics from the stress of gastric juice and intestinal juice. At the same time, it can ensure the reasonable release of the probiotics from the coaxial nanofibers under alkaline conditions, thereby improving the functional effect of the probiotic product. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 The SEM images and diameter distributions of nanofibers with different shell speeds; A is a uniaxial nanofiber; B is a coaxial nanofiber prepared with a flow rate ratio of 1:1 between the core solution and the shell solution; C is a coaxial nanofiber prepared with a flow rate ratio of 1:1.5 between the core solution and the shell solution; and D is a coaxial nanofiber prepared with a flow rate ratio of 1:2 between the core solution and the shell solution.

[0024] Figure 2 The fluorescence inversion images of uniaxial and coaxial nanofibers; A is a uniaxial nanofiber; B is a coaxial nanofiber prepared by a flow rate ratio of 1:1 between the core layer solution and the shell layer solution; C is a coaxial nanofiber prepared by a flow rate ratio of 1:1.5 between the core layer solution and the shell layer solution; and D is a coaxial nanofiber prepared by a flow rate ratio of 1:2 between the core layer solution and the shell layer solution.

[0025] Figure 3 TEM images of uniaxial core layer and coaxial nanofibers; A is a uniaxial nanofiber; B is a coaxial nanofiber prepared by a flow rate ratio of 1:1 between the core layer solution and the shell layer solution; C is a coaxial nanofiber prepared by a flow rate ratio of 1:1.5 between the core layer solution and the shell layer solution; and D is a coaxial nanofiber prepared by a flow rate ratio of 1:2 between the core layer solution and the shell layer solution.

[0026] Figure 4 It is the laser confocal image of the coaxial nanofiber; A is the dark field of the shell layer; B is the dark field of the core layer; C is the bright field of the coaxial nanofiber, and D is the superposition of the bright and dark fields of the coaxial nanofiber;

[0027] Figure 5 Fourier transform infrared spectra of uniaxial and coaxial nanofibers and different powder sample spectra; A is coaxial and uniaxial nanofibers, 1:2 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:2, 1:1.5 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:1.5, 1:1 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:1, and the single core layer is a uniaxial nanofiber; B is a powder sample;

[0028] Figure 6XRD spectra of uniaxial and coaxial nanofibers and different powder samples; A is coaxial and uniaxial nanofibers, 1:2 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:2, 1:1.5 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:1.5, 1:1 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:1, and the single core layer is a uniaxial nanofiber; B is a powder sample;

[0029] Figure 7 are TGA curves and DTG curves of uniaxial and coaxial nanofibers and powder samples; wherein A is TGA of uniaxial and coaxial nanofibers; B is DTG of uniaxial and coaxial nanofibers; C is TGA of powder samples; D is DTG of powder samples; 1:2 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:2, 1:1.5 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:1.5, 1:1 is the coaxial nanofiber prepared when the core-shell flow rate ratio is 1:1, and the single core layer is a uniaxial nanofiber;

[0030] Figure 8 Schematic diagram of the coaxial electrospinning equipment. DETAILED DESCRIPTION

[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0032] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0033] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0034] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0036] Lactobacillus plantarum 69-2 (abbreviated as L. plantarum 69-2) has been published by “Lactobacillus plantarum 69-2 Combined with Galacto-Oligosaccharides Alleviates D-Galactose-Induced Aging by Regulating the AMPK / SIRT1 Signaling Pathway and Gut Microbiota in Mice”, WanWang, Fei Liu, etc.

[0037] The composition of the MRS liquid culture medium used in the embodiment of the present invention is: peptone 10.0 g / L, beef powder 5.0 g / L, glucose 20.0 g / L, yeast powder 4.0 g / L, sodium acetate 5.0 g / L, dipotassium hydrogen phosphate 2.0 g / L, magnesium sulfate 0.2 g / L, ammonium citrate tribasic 2.0 g / L, manganese sulfate 0.05 g / L and Tween 80 1.0 mL / L.

[0038] Example 1 Effect of core-shell flow rate on the performance of coaxial nanofibers encapsulating L. plantarum 69-2 and dihydromyricetin

[0039] 1. Preparation of coaxial electrospinning solution

[0040] (1) Preparation of core layer spinning solution

[0041] A certain amount of polyvinyl alcohol (PVA) was weighed into deionized water, and a 10% (w / v) PVA solution was prepared under magnetic stirring at 95°C. A certain amount of fucoidan (FUC) was weighed and added to the PVA solution and stirred for 15 minutes, so that the concentration of FUC in the PVA / FUC solution was 3%. Then 0.16% (w / v) dihydromyricetin (DMY) was added to the PVA / FUC solution and completely dissolved under magnetic stirring at 75°C to obtain a mixed solution of the three. 200 μL of L. plantarum 69-2 was inoculated into sterile MRS broth and incubated at 37°C for 20 hours. Subsequently, the culture was centrifuged at 6000×g and 4°C for 5 minutes. The cells were washed three times with PBS, and the L. plantarum 69-2 bacterial solution was added to the PVA / FUC / DMY solution and stirred evenly to obtain the PVA / FUC / L. plantarum 69-2 / DMY electrospinning solution (also called core layer solution or uniaxial nanofiber). The effective viable bacterial count of L. plantarum 69-2 in the electrospinning solution was 10 9 -10 10 lg CFU / mL.

[0042] (2) Preparation of shell solution

[0043] Ethyl cellulose powder was added to acetic acid and stirred overnight to obtain a shell solution. The concentration of ethyl cellulose in the shell solution was 40% (w / v), and magnetic stirring was performed at room temperature for 1 hour.

[0044] 2. Effect of core-shell flow rate on the number of live cells of embedded L. plantarum 69-2

[0045] Based on the method proposed by Laelorspoen et al. and Feng et al., the effect of different core-shell flow rates on the viable count of L. plantarum 69-2 embedded in coaxial fibers was evaluated. 10 mg of uniaxial core layer PVA / FUC / DMY fibers loaded with L. plantarum 69-2 (i.e., PVA / FUC / L. plantarum 69-2 / DMY electrospinning solution) and coaxial embedded L. plantarum 69-2 nanofibers with different core-shell flow rates were added to 4.9 mL of PBS buffer solution (pH = 7.4), 400 μL of PBS buffer solution dissolving the coaxial fibers was drawn and added to 20 mL of MRS liquid culture medium, activated at 37 ° C for 24 h, and then the viable count of L. plantarum 69-2 was detected according to the pouring method in the national standard GB4789.2-2016, and each dilution sample was tested in parallel three times.

[0046] 3. Preparation of coaxial nanofibers for improving gastrointestinal resistance of probiotics

[0047] The coaxial electrospinning device consists of a high-voltage power supply, two injection propellers, a receiving end (receiving plate) and a coaxial needle (with inner diameters of 0.50 mm and 1.16 mm (21G-16G), purchased from Shanghai Hongshuo Electronics Co., Ltd.). The structure of the device is as follows Figure 8 As shown, part of the structure of the device has been disclosed in the Chinese patent "202410002887.1", the only difference is that the device used in the present invention has two injection propellers, and the needle is replaced by a coaxial needle. The PVA / FUC / L.plantarum 69-2 / DMY electrospinning solution is added to the inner diameter, and the shell solution is added to the outer diameter. The following parameters were used for the electrospinning process: the injection rate was a flow rate ratio of 1:1, 1:1.5 and 1:2 for the core layer and the shell layer (core layer injection rate 0.6mL / h), the voltage was 17kV, and the needle tip-collector distance was 15cm. At the same time, under the conditions of ambient temperature 25±1℃ and relative humidity 50±2%, the coaxially embedded L.plantarum 69-2 nanofibers prepared at different core-shell flow rates were collected on a 15×15cm aluminum foil.

[0048] 4. Effect of core-shell flow rate on the characterization of coaxial nanofibers co-encapsulated with L. plantarum 69-2 and dihydromyricetin

[0049] (1) Scanning electron microscopy (SME)

[0050] Take the aluminum foil with fibers, cut the fibers together with the aluminum foil into 8mm×5mm rectangles with scissors, stick them on the stage of the scanning electron microscope with double-sided tape, spray gold on the surface, and observe the morphology and thickness of the nanofibers with a scanning electron microscope. The parameters of the scanning electron microscope are an acceleration voltage of 5kV and a magnification of 10000 times. 100 fibers were randomly selected from the scanning electron microscope image, and the morphology and diameter distribution of different treatments (PVA / FUC / L.plantarum 69-2 / DMY electrospinning solution and coaxial electrospinning solution of coaxially embedded L.plantarum 69-2 with different core-shell flow rates) were measured using ImageJ software.

[0051] (2) Transmission electron microscopy (TEM)

[0052] Before observation, the copper mesh was fixed to the collector. When a thin layer of white fibers was observed on the copper mesh, the copper mesh was placed on the stage of the TEM to observe the core-shell structure of the sample.

[0053] (3) Confocal laser scanning microscopy (CLSM)

[0054] Based on the method proposed by Zhong et al., 2 mg of biotin and 1 mg of rhodamine powder were weighed and then placed in the shell layer and core layer solutions respectively, and spun according to the method in step "3. Preparation of coaxial nanofibers for improving the gastrointestinal resistance of probiotics". After completion, the collected coaxial nanofibers were placed under a confocal laser scanning microscope to characterize the fiber structure.

[0055] (4) Fluorescence inverted microscope observation

[0056] The L. plantarum 69-2 bacterial solution was evenly mixed with 5 μg / mL rhodamine 123, then cultured at 37°C in the dark for 30 min. After washing with PBS, the labeled L. plantarum 69-2 cells in the uniaxial core layer fibers and coaxial nanofibers prepared with different core-shell flow rates were observed under a fluorescent inverted microscope in the dark.

[0057] (5) Attenuated Total Reflection Fourier Transform Infrared Spectroscopy (ATR-FTIR)

[0058] Fourier transform infrared spectra were measured by Fourier transform infrared spectrometer for PVA, ethyl cellulose powder (EC), FUC, L. plantarum 69-2, uniaxial core layer PVA / FUC / DMY fibers embedded with L. plantarum 69-2, and coaxial embedded L. plantarum 69-2 nanofibers with different core-shell flow rates. The resolution of all spectra was 4 cm -1 , wavelength range is 4000cm -1 -500cm -1 , scanned 32 times in total.

[0059] (6) XRD analysis

[0060] The crystal structures of PVA, EC, L. plantarum 69-2, uniaxial nanofibers embedded with L. plantarum 69-2, and coaxial nanofibers prepared at different core-shell flow rates were studied by XRD. Cu-Kα radiation was used at 40 kV and 30 mA. The scanning range was 5°-85° (2θ) and the scanning rate was 2° / min.

[0061] (7) Thermal performance analysis

[0062] The thermal stability of coaxial nanofibers prepared with PVA, EC, L. plantarum 69-2, uniaxial core-layer PVA / FUC / DMY fibers embedded with L. plantarum 69-2, and different core-shell flow rates was evaluated by thermogravimetric analysis. A crucible containing 10 mg of sample was heated from 25 °C to 700 °C at a heating rate of 10 °C / min in a nitrogen environment.

[0063] 5. Effect of core-shell flow rate on the antioxidant capacity of coaxial nanofibers co-encapsulated with L. plantarum 69-2 and dihydromyricetin

[0064] 10 mg of fiber sample was dissolved in 1 mL of PBS buffer (pH = 7.4) and then vortexed for 10 min to obtain a solution containing the sample, which was used to measure the ABTS of uniaxial nanofibers embedded with L. plantarum 69-2 and coaxial nanofibers prepared at different core-shell flow rates. + And determination of DPPH free radical scavenging rate.

[0065] (1) DPPH method:

[0066] Accurately weigh 0.0394g of DPPH (M = 394.32g / moL) and dilute to 100mL with ethanol solution to prepare 1mmol / L DPPH mother solution. When measuring, dilute 10 times with ethanol (take 1mL and add 9mL ethanol). Mix 1mL of the solution containing the sample with 5mL of DPPH (0.1mM) solution, protect from light (15min) and measure the absorbance at 517nm. The calculation formula of DPPH free radical scavenging rate is as follows:

[0067]

[0068] Wherein, A0: absorbance of solution containing only DPPH; Af: absorbance of solution containing sample.

[0069] (2) ABTS method:

[0070] 1) Reagents:

[0071] ①ABTS (7mmol / L): Take 384.076mgABTS and dilute to 100mL with distilled water;

[0072] ② Potassium persulfate (140mmol / L): Take 3.78434g of potassium persulfate and dilute to 100mL with distilled water.

[0073] 2) ABTS preparation:

[0074] Mix 5 mL ABTS with 88 μL potassium persulfate and react at room temperature in the dark for 14 h to form ABTS + The free radical stock solution was then diluted 45 times with a PBS solution of pH = 7.4, and the absorbance at a wavelength of 734 nm was (0.7 ± 0.02) before use. The calculation formula for the ABTS free radical scavenging rate is as follows:

[0075]

[0076] Where A0: absorbance of solution containing only ABTS; Af: absorbance of solution containing sample.

[0077] 6. Effect of core-shell flow rate on the viability of coaxial nanofiber-encapsulated L. plantarum 69-2 under simulated gastrointestinal digestion conditions

[0078] The formula of gastric juice was slightly modified based on the method proposed by Minekus et al.: 0.138 mL of potassium chloride solution (0.5 mol / L), 0.018 mL of potassium dihydrogen phosphate solution (0.5 mol / L), 0.25 mL of sodium bicarbonate solution (1 mol / L), 0.236 mL of sodium chloride solution (2 mol / L), 0.008 mL of magnesium chloride hexahydrate solution (0.5 mol / L), add water to a total volume of 10 mL, adjust the pH to 3.0 with 6 mol / L hydrochloric acid solution, add 0.1 g of pepsin, and stir until dissolved.

[0079] The formula of simulated intestinal fluid was slightly modified according to the method of Chinese Pharmacopoeia: 0.068 g of potassium dihydrogen phosphate was weighed and dissolved in 10 mL of water, 1 mol / L sodium hydroxide solution was used to adjust the solution pH to 6.8, 0.1 g of trypsin was added, and stirred evenly until completely dissolved.

[0080] Unencapsulated L. plantarum 69-2, uniaxial nanofibers encapsulated with L. plantarum 69-2, and coaxial nanofibers prepared with different core-shell flow rates were cultured in simulated gastric fluid and simulated intestinal fluid, and the culture conditions were as follows: 37°C, 100 rpm on a shaker for 2 h. 100 μL of the differently treated solutions were diluted 10 times with PBS buffer solution, and the number of viable bacteria was detected according to the plate count method in the national standard GB4789.2-2022. Each dilution sample was tested three times in parallel.

[0081] 7. Results

[0082] (1) Effect of core-shell flow rate on viable count of L. plantarum 69-2

[0083] The results are shown in Table 1. When L. plantarum 69-2 was embedded in uniaxial nanofibers, the number of viable bacteria decreased by 0.99lgCFU / g and the survival rate was 90.19%. The rapid evaporation of the solvent during the spinning process caused changes in the osmotic pressure inside and outside the cells, resulting in a decrease in the number of viable bacteria. When the core-shell flow rate ratio was 1:1, the number of viable bacteria decreased by 1.47lg CFU / g and the survival rate was 85.45%; when the core-shell flow rate ratio was 1:1.5, the number of viable bacteria decreased by 1.80lg CFU / g and the survival rate was 82.18%; when the core-shell flow rate ratio was 1:2, the number of viable bacteria decreased by 1.98lg CFU / g and the survival rate was 80.40%. With the increase of the shell flow rate, the number of viable bacteria of embedded L. plantarum 69-2 decreased significantly. When the core-shell flow rate ratio was 1:1, the survival rate of L. plantarum 69-2 embedded in the coaxial nanofiber was the highest, at 85.45%. The decrease in the survival rate of probiotics may be due to the evaporation of the coaxial solution, and the evaporated acetic acid affects the activity of probiotics. Although the survival rate decreased, when the coaxial nanofibers were embedded with L. plantarum 69-2, at a core-shell flow rate ratio of 1:2, there was still 8.12±0.05lg CFU / g, which was higher than 10 6 lg CFU / g, which proves that EC can be used to encapsulate probiotics in the coaxial electrospinning process.

[0084] Table 1 Number of viable L. plantarum 69-2 cells embedded in uniaxial nanofibers and coaxial nanofibers

[0085]

[0086]

[0087] Note: Different superscript lowercase letters indicate significant differences in the same column, and different superscript uppercase letters indicate significant differences in the same row (P<0.05).

[0088] (2) Effect of core-shell flow rate on the morphology of coaxial electrospun fibers

[0089] Figure 1The SEM images, fiber diameter distribution and average fiber diameter of uniaxial nanofibers and coaxial nanofibers prepared at different core-shell flow rates. The uniaxial nanofibers are uniform in thickness, smooth on the surface and cylindrical in shape, while the coaxial nanofibers show adhesion as the shell flow rate increases. The flow rate of the uniaxial nanofibers is 0.6 mL / h, and the average diameter of the nanofibers is 284.35 ± 32.68 nm. This is because the spinning voltage increases, the electric field force of the spinning solution in the high-voltage electric field increases, the stretching effect increases, and the fiber diameter decreases. When the shell spinning solution flow rates are 0.6 mL / h, 0.9 mL / h and 1.2 mL / h, the average diameters of the coaxial nanofibers with different core-shell flow rates are 205.21 ± 47.78 nm, 137.77 ± 40.28 nm and 129.46 ± 35.17 nm, respectively. Compared with uniaxial nanofibers, the diameter of the coaxial fibers decreases with the increase of the shell solution flow rate. These results indicate that the presence of the shell solution affects the diameter distribution, size, and shape of the coaxial nanofibers. This is because the outer shell fluid prevents the rapid evaporation of the core solvent, which makes the jet more stable and enables it to extend the jet path and the stretching time before forming nanofibers.

[0090] (3) Observation of the distribution of L. plantarum 69-2 in nanofibers using fluorescence microscopy

[0091] The distribution of L. plantarum 69-2 embedded in uniaxial nanofibers and coaxial nanofibers prepared with different core-shell flow rate ratios under a fluorescent inverted microscope is shown in Figure 2. Figure 2 As shown in the figure. L.plantarum 69-2 was successfully embedded in the nanofibers, showing green fluorescent spots, and distributed along the direction of the nanofibers. Coaxial nanofibers are based on uniaxial nanofibers with a shell composed of EC. When a small part of L.plantarum 69-2 is located on the surface of the core layer fiber, the shell formed by EC can also completely embed it. Therefore, this core-shell structure can make L.plantarum 69-2 be completely embedded in the interior of the nanofibers.

[0092] (4) Transmission electron microscopy observation of the core-shell structure of nanofibers

[0093] Transmission electron microscopy results Figure 3 As shown, Figure 3 TEM images of uniaxial nanofibers and coaxial nanofibers prepared with core-shell flow rate ratio. Figure 3 The uniaxial nanofiber A in the graph is a dense solid structure. Figure 3The middle BD shows the core-shell structure of the coaxial nanofibers, with a dark core layer and a bright shell layer, with a clear boundary. The formation of core-shell structured nanofibers may be attributed to high-speed electrospinning, which prevents the mixing of the two polymer solutions. The difference in color of the coaxial nanofibers is due to the difference in electron density between the core and the shell, with the core layer absorbing more electrons and the shell layer absorbing fewer electrons. For uniaxial nanofibers, this electron density difference was not observed. When the core-shell flow rate ratio was 1:1, 1:1.5 and 1:2, the shell thickness was approximately 64.94nm, 76.75nm and 96.76nm, respectively. As the flow rate of the core solution decreased, the shell thickness increased, indicating that the flow rate ratio of the shell solution to the core spinning solution affected the structure of the obtained nanofibers. These changes were largely caused by the decrease in the yield of polymer solid solutes in the core layer.

[0094] (5) Laser confocal microscopy observation of coaxial nanocore-shell structures

[0095] The results of laser confocal microscopy observations are as follows Figure 4 As shown, biotin and rhodamine B were added to the shell solution and the core spinning solution, respectively, and the shell fibers and the core fibers were green and red, respectively. This indicates that biotin-labeled EC and rhodamine B-labeled core solution exist in the coaxial nanofibers. The fluorescence microscope image ( Figure 4 D) in the figure shows the distribution of the core-shell structure. The successful formation of the nanofiber core-shell structure was verified by confocal laser microscopy. In this experiment, the successful realization of the core-shell structure was confirmed by fluorescence measurement, which is consistent with the TEM observation results.

[0096] (6) Effect of core-shell flow rate on infrared spectra of coaxial nanofibers

[0097] The results of the effect of core-shell flow rate on the infrared spectrum of coaxial nanofibers are shown in Figure 5 As shown, Figure 5 The infrared spectra of different powder samples, uniaxial nanofibers and coaxial nanofibers prepared at different core-shell flow rates. EC powder at 3481 cm -1 There is a characteristic band at 2980cm, representing OH stretching vibration. -1 and 2867cm -1 Corresponding to CH stretching vibration, at 1379cm -1 represents CH bending vibration. In addition, 1026cm -1 The significant peak at 3457 cm indicates the vibration of COC cyclic ether. -1 (OH stretching vibration) shows a characteristic peak. In the DMY spectrum, 3141cm -1 There is a strong absorption at 1652 cm -1The absorption peak at 1357 cm belongs to the carbonyl group. -1 The peak at 2560 cm-1 belongs to the phenolic hydroxyl group. The FTIR spectrum of the coaxial nanofibers prepared with EC as the shell solution is similar, and the peak at 2560 cm-1 belongs to the phenolic hydroxyl group. -1 -2980cm -1 、1450cm -1 -1280cm -1 and showed all the characteristic absorption peaks of EC. This may be because PVA / FUC / L.plantarum 69-2 / DMY was encapsulated in EC, which covered some functional groups of the core layer material, resulting in the failure of the characteristic peaks of PVA / FUC / L.plantarum 69-2 / DMY to appear, which further proved the existence of the shell layer.

[0098] (7) Effect of core-shell flow rate on X-ray diffraction of coaxial nanofibers

[0099] The effect of core-shell flow rate on the X-ray diffraction of coaxial nanofibers is shown in the following figure. Figure 6 As shown, Figure 6 XRD patterns of different powder samples, uniaxial nanofibers, and coaxial nanofibers prepared at different core-shell flow rates. PVA powder shows a sharp diffraction peak at 2θ=18.51°. In the XRD spectrum of FUC powder, it can be seen that there is a broad diffraction peak at 2θ=21.52°, which confirms that it is a non-crystalline material. DMY powder has sharp diffraction peaks at 2θ=13.37°, 14.74°, 23.14°, 30.07°, 35.35°, 36.73°, 40.31°, 57.45°, 62.96°, 64.97°, 67.65°, 75.84°, and 78.48°, which confirms that it is a crystalline material. The spectrum of EC shows two broad peaks at 2θ=8.16° and 20.53°, which is related to its amorphous structure and small crystalline areas. In the XRD patterns of uniaxial nanofibers and coaxial nanofibers, the characteristic crystalline peaks of DMY completely disappeared, indicating that DMY changed from a crystalline structure to an amorphous structure in the nanofibers. Compared with uniaxial nanofibers, the coaxial nanofibers prepared with core-shell flow rate ratios of 1:1, 1:1.5 and 1:2 showed new broad diffraction peaks at 2θ=7.22°, 8.29° and 8.56°, respectively. The intensity of the diffraction peak gradually increased with the increase of shell thickness, and EC was still retained at 2θ=8.16° in the coaxial nanofibers, and the characteristic peaks of PVA also disappeared. These phenomena indicate that the non-covalent interactions between PVA, FUC and DMY in the coaxial nanofibers led to the formation of an amorphous complex.

[0100] (8) Analysis of the thermal properties of coaxial nanofibers by core-shell flow rate

[0101] The results of the thermal performance analysis of coaxial nanofibers by core-shell flow rate are shown in Figure 2. Figure 7 As shown, Figure 7 A and C in the figure are TGA curves of PVA, FUC, DMY, EC, uniaxial nanofibers and coaxial nanofibers prepared at different core-shell flow rates. Figure 7 B and D in the figure are DTG curves. The weight loss of all nanofibers is divided into three stages. The first stage occurs below 100°C, which is mainly caused by the evaporation of water and solvent in the sample, and the weight loss of each sample is small. The DTG curve shows that the maximum weight loss rates of PVA and FUC are 323°C and 185°C in the second stage, and the maximum weight loss rates of EC and DMY are 360°C and 366°C in the third stage. The maximum weight loss rates of uniaxial nanofibers and coaxial nanofibers prepared with core-shell flow rate ratios of 1:1, 1:1.5 and 1:2 appear at 214°C, 215°C, 350°C and 359°C. The thermal stability of coaxial nanofibers is higher than that of uniaxial nanofibers, which may be due to the increase in shell flow rate, the increase in thickness of the EC shell layer, and the increase in thermal stability. This means that the composition of the carrier matrix is ​​highly correlated with the thermal stability of the obtained nanofibers.

[0102] (9) Number of viable bacteria of L. plantarum 69-2 encapsulated and unencapsulated by coaxial nanofibers after simulated gastrointestinal tract

[0103] Table 2 shows the number of viable bacteria of uniaxial nanofibers and coaxial nanofibers prepared with different core-shell flow rates after continuous simulated gastrointestinal digestion. As shown in Table 2, after treatment with simulated gastrointestinal fluid, the number of viable bacteria of unencapsulated L. plantarum 69-2 decreased significantly (P<0.05). After simulated gastric fluid, the number of viable bacteria decreased by 2.88lg CFU / g, and the survival rate was 70.55%. After simulated intestinal fluid, the number of viable bacteria decreased by 3.18lg CFU / g, and the survival rate was 53.91%. After treatment with simulated gastrointestinal fluid, the number of viable bacteria of L. plantarum69-2 embedded in uniaxial nanofibers decreased significantly (P<0.05). The viable counts of L. plantarum 69-2 encapsulated in coaxial fibers prepared with core-shell flow rates of 1:1, 1:1.5 and 1:2 decreased by 1.08lg CFU / g, 0.72lg CFU / g, 0.38lg CFU / g and 0.6lg CFU / g respectively after treatment with simulated intestinal fluid, and the survival rates were 85.62%, 90.76%, 95.10% and 92.34% respectively. Compared with the viable counts of uniaxial nanofibers, the survival rate of L. plantarum 69-2 encapsulated in shell-core was significantly improved in gastrointestinal fluid due to the presence of EC shell (P<0.05). There was no significant difference in the number of viable bacteria of L. plantarum 69-2 in the three groups of coaxial fibers embedded with core-shell flow rates of 1:1, 1:1.5 and 1:2 after treatment with simulated gastric juice (P>0.05). The survival rates of coaxial fibers prepared with a core-shell flow rate of 1:1.5 and a core-shell flow rate of 1:2 after treatment with simulated intestinal juice were significantly higher than those of other groups (P<0.05). The number of viable bacteria in the coaxial nanofibers prepared with a core-shell flow rate of 1:1.5 was the highest at 7.37 lg CFU / g, and the survival rate after simulated gastrointestinal juice was the highest at 88.80%. These results indicate that core-shell nanofibers prepared by coaxial electrospinning technology can better protect probiotics against the stress of gastric and intestinal juices.

[0104] Table 2 Number of viable bacteria in uniaxial and coaxial nanofibers after continuous simulated gastrointestinal digestion

[0105]

[0106]

[0107] Note: Different superscript lowercase letters indicate significant differences in the same column, and different superscript uppercase letters indicate significant differences in the same row (P<0.05).

[0108] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing coaxial nanofibers for improving the gastrointestinal resistance of probiotics, characterized in that: The following steps are involved: (1) mixing a polyvinyl alcohol solution and fucoidan to obtain a PVA / FUC solution; (2) mixing the PVA / FUC solution with dihydromyricetin to obtain a blended solution of the three; (3) mixing the three blended solutions and probiotics to obtain a nuclear layer solution; (4) mixing ethyl cellulose and acetic acid to obtain a shell solution; (5) After placing the core layer solution inside the coaxial needle and placing the shell layer solution outside the coaxial needle, the core layer solution and the shell layer solution are mixed at a flow rate ratio of 1:(1-2) to obtain a solution containing the coaxial nanofibers.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass percentage of polyvinyl alcohol in the polyvinyl alcohol solution is 10%; the mass percentage of fucoidan in the PVA / FUC solution is 3%.

3. The preparation method according to claim 1, characterized in that: In step (2), the mass percentage of dihydromyricetin in the three-mixed solution is 0.16%.

4. The preparation method according to claim 1, characterized in that: In step (3), the effective number of viable bacteria in the nuclear layer solution is 10 9 -10 10 1 g CFU / mL; the probiotic is Lactobacillus plantarum.

5. The preparation method according to claim 1, characterized in that: In step (4), the mass percentage of ethyl cellulose in the shell solution is 40%.

6. A coaxial nanofiber prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the coaxial nanofibers according to claim 6 in the preparation of medicines.

Citation Information

Cited By

  • Embedding method of probiotics

    CN120732173A